Interpretación judicial y tutela efectiva del derecho a la identidad: análisis de la sentencia No. 133-17-SEP-CC de la Corte Constitucional de Ecuador (Jurisprudencia) - Jadán Heredia, Diego (2018)
This paper analyzes the sentence No. 133-17-SEP-CC that the Ecuadorian Constitutional Court knew about the violation of the fundamental rights of a male transsexual person, by the National Direction of the Civil Registry, because this institution prevented his gender change from female to male in his birth registration. The analyzes is divided based on the three legal problems that the Court determines, related to the right to effective judicial protection, the duty to motivate judgments and the right to personal identity. In addition, this paper proposes that the right to freedom be read from the republican tradition, that is, as non-domination, which would help to address cases such as the present from a broader and critical view on the role of the State in the respect of fundamental rights.